Systematic review: Diagnostics, management and outcome of fractures of the posterior process of the talus. Issue 11 (November 2020) - Engelmann, E.W.M.; Wijers, O.; Posthuma, J.J.; Schepers, T.
Highlights: PPTF was often found to be associated with (sub)talar joint dislocation and/or other concomitant lower extremity fractures. Early diagnosis using CT imaging and timely treatment are recommended in order to achieve pre-injury functional outcomes and reduce morbidity. ORIF is recommended in case of (even minimal, >3 mm) displacement, articular involvement or if the fracture extends into the body of the talus. More than two thirds of patients treated with ORIF returned to daily activities and sports without complaints. A significantly higher rate of impaired function and complications were found in the non-operatively, both delayed and timely, treated group. Abstract: Background: Fractures of the posterior process of the talus are rare and frequently overlooked, possibly leading to pseudo-arthrosis and chronic pain. To gain more insight into the diagnosis, treatment and outcome of fractures of the posterior process of the talus (PPTF), a systematic review of the current literature was performed to provide recommendations for the management of PPTF. Methods: A literature search in the electronic databases of PubMed, EMbase, Google Scholar and Cochrane library was performed in January 2020 to identify all clinical studies on PPTF with more than three patients. Amongst other variables, the type of study, number of patients, mechanism of injury, type of fracture (anatomy), imaging modality, treatment, postoperative protocol, outcomes, complications and duration of follow-up were noted for systematic analysis of the available evidence, adherent to the PRISMA guidelines. Results: Seven original studies were included with a total of 66 patients. More than one third of patients presented with a (sub)talar joint dislocation ( n  = 25, 37.9%) and 51.5% sustained associated ipsilateral lower extremity fractures ( n  = 34). Delayed diagnosis occurred in 36.4% of patients ( n  = 24). Out of 48 patients with outcome data available, 41.7% ( n  = 20) reported impaired function. In the non-operative group, 64.7% ( n  = 11) had impaired functional outcome, compared to 33.3% ( n  = 6) in the ORIF group, and 30.8% ( n  = 4) in the fragment excision group ( p < 0.001). One third of the patients developed one or more complications ( n  = 25, 37.9%), mostly found in the non-operatively treated group (73.7%, n  = 14) compared to ORIF (25.0%, n  = 8, p < 0.001). Conclusion: Early recognition and timely treatment is warranted in order to achieve pre-injury functional outcome and reduce morbidity. Given the significantly higher complication rate and lower return to the previous level of functionality reported after non-operative treatment, ORIF is recommended if there is (even minimal) displacement, articular involvement or if the fracture extends into the talus body.